1998
DOI: 10.1046/j.1365-2036.1998.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Does eradication of Helicobacter pylori impair healing of nonsteroidal anti‐inflammatory drug associated bleeding peptic ulcers? A prospective randomized study

Abstract: Background: Despite the widely accepted view that Helicobacter pylori is the most important cause of peptic ulcer disease, recent studies have suggested that the microbe protects against nonsteroidal anti‐inflammatory drug (NSAID)‐associated gastroduodenal lesions and promotes ulcer healing. We investigated the effects of H. pylori eradication on the healing of NSAID‐associated bleeding peptic ulcers. Methods: Chronic NSAID users presenting with peptic ulcer haemorrhage underwent endoscopy to secure haemostasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 18 publications
1
31
0
1
Order By: Relevance
“…6 Several controversies regarding H. pylori eradication in patients using NSAIDs still prevail. [7][8][9][10][11][12][13][14] Whether to attempt H. pylori eradication in patients receiving long-term treatment with NSAIDs remains controversial. Some reports advocate H. pylori eradication before NSAID therapy in order to reduce NSAID-induced peptic ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…6 Several controversies regarding H. pylori eradication in patients using NSAIDs still prevail. [7][8][9][10][11][12][13][14] Whether to attempt H. pylori eradication in patients receiving long-term treatment with NSAIDs remains controversial. Some reports advocate H. pylori eradication before NSAID therapy in order to reduce NSAID-induced peptic ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…To confi rm the interaction between the two factors, it is necessary to conduct an interventional study determining the effects of H. pylori eradication on ulcer healing, but no conclusive evidence has been presented. [2][3][4] Although levels of gastric acid secretion have increased among Japanese, they are still lower when compared with those of Westerners. Sakamoto et al 7 reported a case-control study on the association of upper gastrointestinal bleeding and NSAIDs in Japan.…”
Section: Relationship Between Nsaids Ulcer and H Pylori Infectionmentioning
confidence: 97%
“…BianchiPorro et al 2 administered 40 mg/day omeprazole to H. pylori(−) patients with gastric ulcers, H. pylori(+) patients with gastric ulcers, and H. pylori-eradicated patients with gastric ulcers, and documented no significant differences in healing rates among the three groups: 4-week healing rates were 68%, 66%, and 68%, respectively, and 8-week healing rates were 76%, 90%, and 76%, respectively. Chan et al 3 divided H. pylori(+) patients with gastric ulcers into those with H. pylori infection and those in whom H. pylori was eradicated, and reported that, with 20 mg/day omeprazole, the 8- week healing rate for the two groups was 84% and 72%, respectively. Although the healing rate for the H. pylorieradicated patients was slightly lower, there was no signifi cant difference.…”
Section: Helicobacter Pylori Eradication and Gastric Ulcer Healingmentioning
confidence: 98%
See 1 more Smart Citation
“…Chan et al 65 performed a large prospective randomized study of ulcer healing in 195 H. pylori-infected patients who presented with ulcer hemorrhage. Patients were treated with 8 weeks of omeprazole and 1 week of triple therapy (bismuth, tetracycline, and metronidazole eradication therapy) or placebo.…”
Section: Cohort Studiesmentioning
confidence: 99%